Comparative study of conventional and liquid-based cytology in a population with opportunistic cytological screening. - Hadzi-Nicheva, Biljana; Grncharovska, Zlata; Prodanova, Irina; Yashar, Genghis; Kubelka-Sabit, Katerina; Popovska, Zora; Basheska, Neli (Springer, 2005)
Background: In the last decade the conventional Pap smear (CPS) has frequently been replaced by the liquid-based cervical cytology (LBC) in the routine clinical practice due to improved technical quality and increased efficacy in detecting squamous intraepithelial lesions (SIL) and cervical cancer by LBC. Aims: The purpose of this study is to report the preliminary results of the of the performances of LBC versus those of CPS, in a country with an opportunistic cytological screening and a high incidence of cervical carcinoma. Methods: This comparative retrospective study is an initial part of a wider project, anticipated to assess the validity of the new method and its impact on clinical practice. It includes two groups of women referred to a tertiary centre for gynaecologic care, in different six-month periods. In each group, the Pap smear was taken by one of the methods. Data from unselected, consecutive series of 3,261 LBC tests and of 4,102 CPSs were analysed. Cytological diagnoses were classified using the Bethesda system. The differences in specimen adequacy and the rates of atypical squamous cells (ASC) category between the two groups were compared using chi-sqare test. The histological correlation with histopathological findings could be established in 901 patients with the LBC and in 1,408 with the CPSs. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and diagnostic accuracy of the findings were evaluated as well. Results: The improvement in the specimen adequacy for LBC was documented by the more than fivefold reduction of the proportion of unsatisfactory specimens (0.4% for LBC vs. 2.1% for CPS, P<0.001). The rate of "satisfactory but limited by¨ was also reduced by 40% for LBC (P<0.001). However, the rate of ASC category was similar in both methods (0.9% for LBC vs. 1.2% for CPS). The performances of LBC for detection of cervical SIL or cancer lesions versus those of CPS, such as sensitivity (94% vs. 79%), PPV (85% vs. 69%) and NPV (90% vs. 66%) were significantly different (P<0.001). There was no statistically significant difference in specificity between the methods (65% vs. 62%, P<0.15). Ultimately, the diagnostic accuracy was higher in LBC than in CPS (84% vs. 73%, P<0.001). Conclusions: Our preliminary results suggest that the implementation of LBC significantly improved the technical quality of the smears and resulted in statistically significant improvement of the diagnostic value of the Pap test.
Keywords: cervical carcinoma; squamous intraepithelial lesions (SIL); cytological screening; conventional Pap smear; liquid-based cervical cytology; adequacy; diagnostic accuracy